Rozwiązania w zakresie wspierania MSP w Niemczech - Kicior, Karolina (Financial Assistance for Small and Medium Enterprises in the Federal Republic of Germany, 2008)
Lots of changes have been recently introduced into the politics, which support small and medium enterprises in Germany. In the 50s and 60s there was the trend to liquidate disadvantageous conditions for small and medium enterprises. In the 70s and 80s the ability for sectors subject innovation and their contribution to the structural changes were emphasized. Currently German economic market foster economic independence for small and medium enterprises and create new workplaces. Six thematic areas to support SMEs were separated by German Ministry of Economics. The author also introduce forms of assistance, financial aid and institutions supporting German entrepreneurs. From the point of view of SMEs, the most important are the following programmes: the ERP programme that support creating new businesses by providing financial aid and also "Improvement of Regional Economic Structure". This article is not only about institutions supporting enterprises, but also about benefits resulting from that sector.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 253-269